Magnetic and electronic properties of the RECu4Al8 (RE = Tb, Dy, Ho, and Er) intermetallic compounds. (April 2022) - Mercena, S.G.; Melo, A.T.; Lima, A.F.
Abstract: Spin density functional theory calculations were employed to study some of the magnetic and electronic properties of the RECu4 Al8 (RE = Tb, Dy, Ho, and Er) intermetallic compounds in their tetragonal crystal structure and their collinear antiferromagnetic state. The exchange and correlation electronic effects were treated by both a generalized gradient approximation (GGA) in its recently revised version for solids (GGA-PBEsol), and the addition of the effective Hubbard U term (GGA-PBEsol + Ueff ) in the RE 4f states. Based on these methodologies, the total magnetic moment of the RE atoms and their spin and orbital contributions were determined. The total magnetic moment calculated with GGA + PBEsol (Ueff = 0.0 eV) agreed with the experimental data, except for the TbCu4 Al8 system, in which the addition of the Ueff term was needed for a better description. Using GGA + PBEsol, the magnetocrystalline anisotropy energy (MAE), easiest magnetization axis (EMA), exchange splitting of the RE 4f states (Δex ), and the electronic specific heat coefficients (γ) of the four compounds were determined. The values of the MAE found for TbCu4 Al8, DyCu4 Al8, HoCu4 Al8, and ErCu4 Al8 were 3.13, 9.11, 26.93, and 17.41 meV/f.u., respectively. The EMA for TbCu4 Al8, DyCu4 Al8, and HoCu4 Al8 was found to be [111], while for ErCu4 Al8 it was [001]. The values of Δex were equal to 4.3, 3.6, 2.8, and 1.9 eV for TbCu4 Al8, DyCu4 Al8, HoCu4 Al8, and ErCu4 Al8, respectively. Highlights: Spin density functional theory was used to study RECu4 Al8 (RE = Tb, Dy, Ho, and Er). Exchange and correlation electronic effects are treated with the GGA-PBEsol + U method. Computed total magnetic moment values for RE atoms agree with experimental data. Easiest magnetization axes and electronic specific heat coefficients were determined.